Pengaruh Pendekatan Problem Based Learning (PBL) terhadap Kemampuan Berpikir Kreatif Matematis Siswa Kelas X SMK Putra Anda Binjai - Dira Puspita Sari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This study aims to determine whether there is an influence on students' mathematical creative thinking abilities who are taught using the Problem Based Learning (PBL) model with students using conventional learning. This research was carried out at SMK Putra Anda Binjai in the 2019/2020 academic year. The method used in this research is quasi-experimental. Sampling was done by purposive sampling. The research sample consisted of 60 students consisting of 30 students in the experimental class and 30 students in the control class. The research instrument given was in the form of a test consisting of 5 description questions. Based on the results of the study, the average score of students taught by the Problem Based Learning (PBL) learning model was higher than the average score of students taught by conventional learning. This can be seen from the average value of the experimental class 60.00 and the average value of the control class 51.00. The results of the calculation of data analysis using the t test with a value of t_count t_table (0,306 1,671) with degrees of freedom dk = 30, with a significant level of 0.05. Thus H0 is rejected and Ha is accepted, which means that the students' mathematical creative thinking ability in the experimental class is greater than the mathematical creative thinking ability of students in the control class. This means that there is an effect of using the Problem Based Learning (PBL) learning model on the mathematical creative thinking ability of class X students of SMK Putra Anda Binjai.